2015
DOI: 10.1166/jnn.2015.9509
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility Assessment of Polyethylene Glycol-Poly L-Lysine-Poly Lactic-Co-Glycolic Acid Nanoparticles <I>In Vitro</I> and <I>In Vivo</I>

Abstract: The present study was designed to evaluate the biocompatibility of nanoparticles polyethylene glycol (PEG)-poly L-lysine (PLL)-poly lactic-co-glycolic acid copolymer (PLGA) (PEG-PLL-PLGA) before clinical application. We applied some tests to assess the safety of PEG-PLL-PLGA nanoparticles (NPs). There was low cytotoxicity of PEG-PLL-PLGA NPs in vitro as detected by MTT assay. Cell apoptosis and intracellular accumulation of PEG-PLL-PLGA were determined by FCM assay. The apoptotic rate induced by nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The results of this study showed the absence of cytotoxic effects from HA/ PLGA and Bonefill ® eluates, which are in accordance with literature demonstrating HA, bovine bone, and PLGA as biocompatible materials (Galia et al, 2008;Cieślik et al, 2009;Trif et al, 2015). PLGA nanoparticles associated with polyethylene glycol (PEG) and poly L-lysine (PLL) (PEG-PLL-PLGA) have demonstrated low cytotoxicity by MTT assay (Guo et al, 2015).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study showed the absence of cytotoxic effects from HA/ PLGA and Bonefill ® eluates, which are in accordance with literature demonstrating HA, bovine bone, and PLGA as biocompatible materials (Galia et al, 2008;Cieślik et al, 2009;Trif et al, 2015). PLGA nanoparticles associated with polyethylene glycol (PEG) and poly L-lysine (PLL) (PEG-PLL-PLGA) have demonstrated low cytotoxicity by MTT assay (Guo et al, 2015).…”
Section: Resultssupporting
confidence: 91%
“…Studies concerning the impact of these nanostructures on living organisms and the environment are therefore needed so that the safety of these nanosystems can be assessed before they become even more widely commercialized (De Lima et al, 2011). For example, the aforementioned PEG-PLL-PLGA showed no blood toxicity and mutagenicity by MN (Guo et al, 2015). Positively charged PLGA nanoparticles led to chromosomal aberrations without primary DNA damage in human bronchial epithelial cells (Platel et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of toxicity results from our previous studies, 13,14 we plated 4×10 5 /mL cells in six-well plates and incubated with 1.0 μg/mL equivalents of DNR in NIR797-labeled NPs for 12 and 36 hours. After washing the plated cells twice with cold PBS (1,000 rpm, centrifuge for 5 minutes), 500 μL of the binding buffer was added, followed by 5 μL annexin V-FITC at room temperature, and protected from light for 15 minutes.…”
Section: Nir797-labeled Nps In Vitro and In Vivomentioning
confidence: 99%
“…Our previous studies have demonstrated PEG-PLL-PLGA NPs with high efficiency and low toxicity. 13,14 Thus, in the present study, we wanted to demonstrate the potential synergistic effects of DNR-Tet-NPs and Tf in leukemia cells. Evidenced by NIR imaging experiments, drug accumulation at the tumor site of DNR-Tet-Tf-NPs group was obviously higher than in the DNR-Tet-NPs group, suggesting that Tf-modified NPs have targeted antitumor effect.…”
mentioning
confidence: 99%
“…Petrilli and colleagues showed that the in vitro cytotoxicity on L929 cells of liquid crystalline nanodispersions complexed with short‐interfering RNAs was consistent with the results obtained in in vivo studies of skin irritation carried out with hairless mice . Moreover, the cytotoxicity of polyethylene glycol‐poly‐ l ‐lysine‐poly‐lactic‐ co ‐glycolic acid copolymer nanoparticles evaluated by the 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyl tetrazolium bromide (MTT) assay using L929 cells was similar to the acute toxicity evaluated in Kunming mice . Therefore, in vitro cytotoxicity studies conducted with L929 cells can predict in vivo studies.…”
Section: Cytotoxicity Of Cncs: a Critical Evaluation Of The Biocompatmentioning
confidence: 83%